(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Study aims to determine the rate and clarify some valuable clinical features in predicting difficult intubation in patients undergoing maxillofacial abscess surgery. Objects and methods: Prospective, descriptive study involved 347 patients with facial abscesses who undergoing surgery at the Central Maxillofacial Hospital in Hanoi from August 2023 to October 2024. Results: The average age of the patients is 48.92 ± 18.02 years; the ratio of male to female in the research is 3/1,8. The most common sites of abscesses are masseter muscle abscesses (43,5%), submandibular abscesses (25,4%), and submandibular - floor of mouth - lateral pharyngeal wall abscesses (20,8%). The rate of difficult endotracheal intubation are 46,97%. Factors such as jaw tightness, difficulty swallow, difficulty breathing hoarseness, loss of the lower jaw’s bony margin and limited tongue movement are found to be significant predictive factors (p < 0.001). Conclusions: The rate of difficult endotracheal intubation is 46.97%. The predictive factors in difficult intubation including jaw tightness, airway obstruction and swelling of the floor of mouth - lateral pharyngeal wall.